Epigenetics and Cancer: A Comprehensive Review - Pathak, Ayush; Tomar, Sarthak; Pathak, Sujata (Asian Pacific Journal of Cancer Biology, 2023)
Cancer is a disease with extraordinary clinical significance, with much of medical research being devoted to it. Innumerable factors are relevant in fully understanding cancer but the epigenetic aspect stands out. Epigenetics is the study of changes, often germ-line, to the genome affecting the gene expression by silencing certain genes and modifying the gene expression. The three primary mechanisms for epigenetic changes are DNA methylation, histone modification and non-coding RNA (ncRNA) associated gene silencing. While epigenetics is a pivotal mechanism for the regular maintenance of a myriad of processes- including in cell differentiation and adaptability- aberrant epigenetic changes can lead to depreciated/altered gene function which may ultimately culminate in cancer. Consequently, the connection between epigenetics and cancer has been intensely studied over the past two decades and has generated substantial clinical data attesting to the efficacy of epigenetics as a viable approach to understand cancer progression or therapy. In this review, we look at the fundamental epigenetic principles, the changes in the epigenome which can often be a precursor to cancer, analyse the increasingly important role of epigenetics in decoding carcinogenesis, explore the latest advancements in use of epigenetics in cancer therapy and how the reversible nature of these epigenetic changes have changed the way we approach cancer therapy.